CMOS-compatible nanowire sensor arrays for detection of cellular bioelectricity - Chen, Peng (2012)
Perfectly aligned arrays of long silicon nanowires fabricated using a top–down complementary metal oxide semiconductor (CMOS) compatible approach and their ability for real-time extracellular recording of cellular bioelectricity are presented. The technique enables noninvasive, high-sensitivity, high-throughput, long-term electrophysiology measurements at the single-cell level or from tissues.